Fabrication of SiC and h-BN particle-reinforced Cu-Sn-Zn sliding alloy by powder metallurgy and characterization - Devecili, Ahmet Oktay; Bakkaloglu, Adem; Gencer, Yucel (REDAKCIA KOVOVE MATERIALY, 2024)
In this study, samples were produced by powder metallurgy, adding 0.25 wt.% h-BN and 0.25, 0.5, 1, 2, 4, and 5 wt.% SiC to Cu, Zn, and Sn metallic powder mixtures. The samples were mixed using high-energy mechanical alloying and compacted under a 400 N mm-2 pressure. Subsequently, they were sintered for 2 h at 820 degrees C in a controlled atmosphere furnace. Characterization processes included hardness measurement, XRD analysis, dimensional changes, and electron and optical microscopy. The results of the study revealed that the dimensional change after sintering increased initially with the addition of SiC and then decreased as the addition amount increased. XRD analysis identified characteristic peaks of the reinforcement materials and the metallic matrix. SEM analysis confirmed the distribution of h-BN and SiC within the metallic matrix. Wear resistance was significantly improved with increasing SiC addition in the 3 N load wear tests, remaining unchanged in the 1 N load wear tests. Furthermore, an increase in SiC content led to consistent friction coefficients at each stage of the wear test, while SiC-free samples exhibited load-dependent changes in friction coefficients.
Keywords: powder metallurgy; wear; mechanical alloying; SiC; h-BN; WEAR BEHAVIOR; TRIBOLOGICAL BEHAVIOR; MECHANICAL-PROPERTIES; MATRIX COMPOSITES; GRAPHITE; FRICTION; Materials Science; Metallurgy & Metallurgical Engineering